Loss Aversion - Taisuke Imai; Klaus Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Loss aversion postulates that people prefer avoiding losses over acquiring gains of equal size. It is a central part of prospect theory and, according to Daniel Kahneman, "the most significant contribution of psychology to behavioral economics" (Kahneman, 2011, p. 300). It has powerful implications for decision theory and has been fruitfully applied in many subfields of economics. However, because the reference point is often not well defined and loss aversion interacts with other behavioral biases, there is some controversy about the concept.
Keywords: 330; loss aversion; reference point; prospect theory; endowment effect; decision theory; risk